(untitled) (Journal of Sustainability and Environmental Management, 2022)
This research was aimed to determine below ground biomass (BGB) of ruderal plants species and soil physicochemical parameters in seven homogenous sample plots in Birnin Kebbi Metropolis of Kebbi State, Nigeria and to assess their importance for energy flow in the ecosystems. Completely Randomize Design was adopted for monthly sampling (June-November 2019) and belowground biomass were collected after removing above ground biomass by digging 40 cm depth to collect fresh BGB in the central 20cm x 20cm quadrat using destructive method which was then oven dried at 650C for 48 hrs. Soil samples were collected between 0-15 cm depths using soil auger for analysis of soil physicochemical parameters using standard methods. Below ground biomass differed significantly between the months (P≤0.05) with gradual increase from a minimum values in June (18.18±0.82 gm-2/month) to a maximum values in October (71.92±1.93gm-2/month) and a decreased in November (61.31±1.36 gm-2/month). There was no significant difference among the sites (P>0.05). Site A, F and C recorded the highest value of Nitrogen (0.15±0.06%, 0.15±0.02% and 0.13±0.11%), Phosphorus (14.07±0.37mg/kg, 12.03±0.33mg/kg and 9.14±0.13mg/kg), Potassium (0.16±0.08 cmol/kg, 0.15±0.11 cmol/kg and 0.12±0.04 cmol/kg) and Organic matter (1.03±0.15%, 0.88±0.33% and 0.76±0.08%) respectively and the result was not statistically different (P>0.05).The research shows that ruderal plants adapted the ecological factors of the study area and provides based line information on below ground Biomass (BGB) of ruderal plants species in Birnin Kebbi town and also provide valuable information on the physical and chemical properties of soil that supports growth and development of the ruderal plants. Further research on the belowground biomass of most dominant ruderal plants in Birnin Kebbi ecological zone should be conducted to assess their contribution in providing land cover and soil compaction which can reduce percolation and carbon sequestration.